Design of Smart Hotstage-Microscopy for Enhancing Thermal Behaviour in Drug Melting Process - Ramadhani, Muhammad; Yudhana, Anton; Budi Setianto, Arif; Mega Reski4, Julia; Cahya Subrata, Arsyad; Jendri; Mufandi, Ilham (Emitor: Jurnal Teknik Elektro, 2025)
The melting point of medicine is an important factor to determine the purity of medicinal raw materials, thermal behavior is closely related to the melting process of that. This research focuses on developing an intelligent Smart Hotstage-Microscopy prototype to observe thermal behavior in the drug melting process. This prototype heats the drug evenly on a hot plate equipped with a polarizing microscope, thermocouple sensor, microcontroller, and LCD display to view the temperature reading results. The performance of the Smart Hotstage-Microscopy prototype was obtained by testing the thermocouple sensor, heating system, cooling system, and drug validation. In this paper the test results show that the thermocouple sensor test has an R2 value of 0.9983, which shows that the correlation between the actual temperature and the hot part temperature shows a significant correlation, which is 99.83%. Testing the heating system from an average temperature of 28.57°C to the average temperature of 298.59°C took an average time of 11.28 minutes. Meanwhile, testing the cooling system took 5.19 minutes to reduce the temperature from average 298.59°C to 33.379°C. This test proves that the prototype of Smart Hotstage-Microscopy can work well in melting drugs